SUICIDE-RELATED OUTCOMES AND DEATH BY DRUG OVERDOSE AND ACCIDENTAL INJURY FOLLOWING PRISON RELEASE IN LATER LIFE. (11th November 2018) - Barry, L; Steffens, D; Covinsky, K; Conwell, Y; Li, Y; Byers, A
Abstract: The number of middle/older-age persons reentering the community following incarceration is growing exponentially, yet little is known about suicide-related outcomes (attempts and deaths) in this population. We conducted a retrospective cohort study (2012–2014) of Veterans age ≥50 who were Medicare enrollees to compare rates of death by suicide, drug overdose, and other accidental injuries and rates of suicide attempt between those reentering the community in later life (N=7, 671) and a matched group of non-incarcerated controls (N=7, 671). We linked the Department of Veterans Affairs National Patient Care Database and Suicide Data Repository, and used linked Medicare data to identify reentry status. We determined rates of each outcome (per 100, 000/year) in the reentry and control groups and used competing risk proportional hazards models adjusted for medical conditions, psychiatric illness, homelessness, and traumatic brain injury to compare their risks. Suicide rates were 30.4 and 17.4 in the reentry and control groups, respectively (HR 2.40; 95%CI 0.51–11.24). Those released from prison also had significantly higher rates of death by drug overdose (121.7 vs. 43.5; HR 3.45; 95%CI 1.37–8.73) and other accidental injury (126.0 vs. 39.1; HR 3.13; 95%CI 1.28–7.69), and increased risk of suicide attempt (599.7 vs. 134.7; HR 3.42; 95%CI 2.22–5.26). Individuals released from incarceration in later life are at considerably higher risk of suicidal behavior and death by drug overdose and accidental injuries as compared with non-incarcerated persons. This study offers benchmark data regarding these mortality outcomes and suicide risk in a growing high-risk population, with implications for targeting prevention and intervention.